2022
DOI: 10.1002/smll.202201602
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Interfacial Nanothermometry Using DNA‐PAINT Microscopy

Abstract: Biofunctionalized nanoparticles are increasingly used in biomedical applications including sensing, targeted delivery, and hyperthermia. However, laser excitation and associated heating of the nanomaterials may alter the structure and interactions of the conjugated biomolecules. Currently no method exists that directly monitors the local temperature near the material's interface where the conjugated biomolecules are. Here, a nanothermometer is reported based on DNA‐mediated points accumulation for imaging nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Moreover, the thermal effect of high-power lasers was observed to damage both the fluorescent dye and the optical system (Figure S19), resulting in conformational changes in biomolecules. This issue has also been reported by previous studies. To address this problem, recent theoretical and experimental studies have demonstrated that utilizing the anapole mode for studying single molecules can eliminate the heating effect. , Furthermore, utilizing the resonantly enhanced near-fields in large all-dielectric cavities using anapole modes may be a potential method to circumvent the heating effect in the current study. Additionally, utilizing hybrid metal-dielectric cavities can generate higher near-field enhancement factors to reduce the loss level, as experimentally demonstrated for nonlinear optical effects .…”
Section: Resultssupporting
confidence: 65%
“…Moreover, the thermal effect of high-power lasers was observed to damage both the fluorescent dye and the optical system (Figure S19), resulting in conformational changes in biomolecules. This issue has also been reported by previous studies. To address this problem, recent theoretical and experimental studies have demonstrated that utilizing the anapole mode for studying single molecules can eliminate the heating effect. , Furthermore, utilizing the resonantly enhanced near-fields in large all-dielectric cavities using anapole modes may be a potential method to circumvent the heating effect in the current study. Additionally, utilizing hybrid metal-dielectric cavities can generate higher near-field enhancement factors to reduce the loss level, as experimentally demonstrated for nonlinear optical effects .…”
Section: Resultssupporting
confidence: 65%
“…With a silicon nitride nano-optomechanical drum resonator as a sensitive thermometer, individual gold nanorods are localized and their spectra and polarization features are fully characterized, additionally shedding light on their interaction with the nanoresonator itself. Among the huge variety of nanoparticle shapes and materials, gold nanorods occupy a relevant position in gas-and liquid-phase chemical detection as well as a sensing platform for biomolecules 21,22 or as photothermal heating sources. 23 In the present study, the plasmonic properties of such nano-objects are analyzed and their corresponding plasmonic damping mechanisms unraveled, showing also a good agreement with finite element method (FEM) simulation results.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Metallic nanoparticles (NPs) exhibit localized surface plasmon resonances that significantly enhance their interaction with light. [1] They are powerful harvesters of the energy of incoming photons, that is concentrated in subwavelength regions, [2] fluorescence (intensity, spectrum, polarization, lifetime), [23] Raman (intensity, spectrum), [24,25] phase transition, [12,26] viscosity, [27] or binding-time [28,29] of a nearby probe in close proximity to the nanosystem. However, these techniques require previous calibrations of the probes and yield a temperature that is not necessarily the same as the NP.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experimental thermometry techniques have been proposed for plasmonics. [ 21,22 ] These techniques primarily involve quantifying a temperature‐dependent property, such as the fluorescence (intensity, spectrum, polarization, lifetime), [ 23 ] Raman (intensity, spectrum), [ 24,25 ] phase transition, [ 12,26 ] viscosity, [ 27 ] or binding‐time [ 28,29 ] of a nearby probe in close proximity to the nanosystem. However, these techniques require previous calibrations of the probes and yield a temperature that is not necessarily the same as the NP.…”
Section: Introductionmentioning
confidence: 99%